Bioprosthetic Aortic Valve Thrombosis and Literature Review - Milan Radovanovic; Charles W. Nordstrom; Richard D. Hanna (Journal of Cardiovascular Development and Disease, 2022)
An 83-year-old gentleman with a history of 23-mm Hancock-II-bioprosthetic aortic valve (BAV) replacement ten-years prior presented with symptoms of dyspnea and lower extremity edema. During the preceding seven-years, he had been noted to have asymptomatic increased mean transvalvular gradients (MG; 36–50 mmHg) felt to be due to either early bioprosthetic degeneration, pannus formation, or patient–prosthesis mismatch. An echocardiogram at the time of symptom development demonstrated significant flow acceleration through the aortic valve, mild regurgitation, and severely increased MG (48 mmHg) with prolonged acceleration time (AT, 140 msec). A trial of warfarin anticoagulation resulted in dramatic improvement after only 6 weeks with laminar flow through the AV, near-total resolution of regurgitation, and a decrease in MG to 14 mmHg and AT to 114 msec. These findings strongly suggest that BAV thrombosis was the predominant mechanism responsible for the longstanding high MG. Our case highlights that BAV thrombosis should be considered in the differential of elevated gradients regardless of the age of prosthesis, and that a trial of warfarin anticoagulation may be beneficial even if elevated gradients have been present for a prolonged period. Valvular gradients are often abnormal long before a formal diagnosis; however, these may reverse quickly with anticoagulation therapy.